The chrysanthemum tiger - Clare, Alys (Clare, Alys. Gabriel Taverner series., 2024)
March, 1605. Country doctor and former ship's surgeon Gabriel Taverner has embarked on his next adventure. Since discovering that the debilitating injury he sustained years ago has lost its power to induce chronic seasickness, he has been impatient to leave Devon once more, and now it is in the service of Walter Haverleigh, a wealthy and successful merchant, who has engaged Gabriel to tend the crew of the Luipaard on her voyage to the Eastern seas. As the months and years of Gabriel's absence continue, his family and friends are struggling with the replacement physician he engaged before his hasty departure. Doctor Maudsley Cheverell has turned out to be incompetent, arrogant and self-serving. When one morning his dead body is found in a ditch, it seems that nobody will mourn him or regret his untimely death.